(3GdLhGgQ GdSfjI aj GdCMGOjK GdbOSjIs - (3GdYGedj, GdMQ, eMeO Hf GdMSf Hf Ydj, J (B1104 (3g`s ((3GdfLa GdCTQas)
(3ChdgG (B:s
(3GdMeO ddg GdPj ChVM aj cdGeg SHjd GdgOGjI (B... (3dG jNai eG dcdGe Gddg SHMGfg ef GdeRjI Ydi cd cdGe aefg JXgQ CfhGQ GdQTGO XghQ GdCfhGQ ef GdCceGe hHg JLdJ TeS GdgOi ef Cab GdfHhI (B...s
(3BNQgG (B:s
.. (3hbO bGd GdTjN aj ehGVY ef cJHg CfG cd MOjK Yed Hg eCNhP ef GdCUhd GdeLeY Ydi UMJgG hbGd GdWHQSj aj cJGH GdGMJLGL eG gh bQjH ef Pdc hcPdc cKjQ ef GdCUMGH (B...(3Jes
(3JGQjN JCdjag (B: (3GdYSTQ GdCNjQ ef QeVGf (B1056 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\90s
(3GdPQjYI (B5\1289s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs